Influence of traumatic brain injury on ipsilateral and contralateral cortical perfusion in mice. (31st January 2023) - Meyer, Simon; Hummel, Regina; Neulen, Axel; Hirnet, Tobias; Thal, Serge C.
Highlights: TBI affects the perfusion of both hemispheres. Contralateral perfusion shows biphasic pattern, first hypoperfusion followed by hyperperfusion. Pathological ipsilateral perfusion suggests inadequate distribution and trigger of further damage. Abstract: Traumatic brain injury (TBI) is one of the most important causes of death in young adults. After brain injury cortical perfusion is impaired by cortical spreading depression, cerebral microvasospasm or microvascular thrombosis and contributes to secondary expansion of lesion into surrounding healthy brain tissue. The present study was designed to determine the regional cortical perfusion pattern after experimental TBI induced by controlled cortical impact (CCI) in male C57/BL6N mice. We performed a longitudinal time series analysis by Laser speckle contrast imaging (LSCI). Measurements were carried out before, immediately and 24 h after trauma. Immediately after CCI cortical perfusion in the lesion core dropped to 10 % of before injury (baseline; %BL) and to 21–24 %BL in the cortical area surrounding the core. Interestingly, cortical perfusion was also significantly reduced in the contralateral non-injured hemisphere (41–58 %BL) matching the corresponding brain region of the injured hemisphere. 24 h after CCI perfusion of the contralateral hemisphere returned to baseline level in the area corresponding to the lesion core, whereas the lateral area of the parietal cortex was hyperperfused (125 %BL). The lesion core region itself remained severely hypoperfused (18 to 26 %BL) during the observation period. TBI causes a maldistribution of both ipsi- and contralateral cerebral perfusion immediately after trauma, which persist for at least 24 h. Higher perfusion levels in the lesion core 24 h after trauma were associated with increased tissue damage, which supports the role of reperfusion injury for secondary brain damage after TBI.